ISLAND TRAGEDY-GLOBAL PROBLEM - Nurkuloba Sevara Akram qizi; Tilavov Davronbek Davlatovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: My article is about the Island Sea, which is the only one in Uzbekistan, and the tragedy of its drying up. I wrote in it about the harmful effects of Island tragedy on the flora and fauna , the environment on incines. I have provided information about the useful side of this dry sea. The president's address to the UN was also mentioned .